2017
DOI: 10.1080/0142159x.2017.1294749
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of mindfulness to reduce stress and burnout among intern medical practitioners

Abstract: Mindfulness interventions may provide medical practitioners with skills to effectively manage stress and burnout, thereby reducing their experience of these symptoms. It is likely that doctors would benefit from the inclusion of such a training program as a part of their general medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 19 publications
5
101
0
Order By: Relevance
“…Furthermore, since participation in the program is time-intense, resident physicians may be dissuaded from choosing to participate. Nevertheless, as mindfulness once learned is not tied to times and places, it can easily and flexibly be implemented into daily life (Ireland et al 2017). In addition to effects of program participation on the level of individual program participants, future studies should evaluate transfer effects onto the participant's environment, for example, by including reports by patients and colleagues.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since participation in the program is time-intense, resident physicians may be dissuaded from choosing to participate. Nevertheless, as mindfulness once learned is not tied to times and places, it can easily and flexibly be implemented into daily life (Ireland et al 2017). In addition to effects of program participation on the level of individual program participants, future studies should evaluate transfer effects onto the participant's environment, for example, by including reports by patients and colleagues.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…First results are promising, but somewhat heterogeneous. Some studies reported decreases in stress or burnout (Ireland et al 2017;Lases et al 2016), whereas other studies failed to find such associations (Goldhagen et al 2015;Verweij et al 2018). The participants of an MBP for surgical resident physicians suggested that the program should have had a stronger focus on their daily medical practice, and the authors conclude that MBPs for resident physicians are probably most effective when tailored to meet this group's particular needs (Lases et al 2016).…”
mentioning
confidence: 99%
“…Ireland et al reported a significant reduction in stress and burnout with a 10-week mindfulness course, though there was no follow up after the training ended. 17 A 5-year follow-up study of medical students trained in mindfulness also demonstrated that participants continued to use mindfulness or relaxation exercises into the future. 18 Mental health problems remain stigmatised in the medical workplace.…”
Section: Mindfulness and Meditation Skills (2)mentioning
confidence: 98%
“…[39][40][41][42] Consistent with these findings, preliminary studies reported beneficial effects of MBIs in residents. [43][44][45] For instance, Rosdahl and others 43 found that a single mindfulness session decreased perceived stress and burnout. Similarly, Lases and others 44 and Ireland and others 45 reported significant decreases in perceived stress and burnout after 5 or 10 sessions of mindfulness.…”
Section: Introductionmentioning
confidence: 99%